Combined With Mefloquine, Resurrect Colistin Active in Colistin-Resistant Pseudomonas aeruginosa in vitro and in vivo - Zhang, Xiaodong; Zhao, Yining; Feng, Luozhu; Xu, Mengxin; Ge, Yiru; Wang, Lingbo; Zhang, Ying; Cao, Jianming; Sun, Yao; Wu, Qing; Zhou, Tieli (Frontiers in Microbiology, 2021)
Colistin is a polymyxin antibiotic that is widely used for the treatment of multidrug resistant (MDR) Pseudomonas aeruginosa infections, as the last resort. Over the past few years, unreasonable use of antibiotics has resulted in an increase in MDR strains, including colistin-resistant P. aeruginosa. The present study aimed to explore the synergistic effects of mefloquine in combination with colistin for the treatment of colistin-resistant P. aeruginosa in vivo and in vitro. The synergistic effect of the combination of mefloquine and colistin was investigated in vitro using checkerboard method, time-killing assay, biofilm formation inhibition test, and biofilm eradication test. The study also explored the synergistic effects of this combination of drugs in vivo, using a Galleria mellonella infection model. The results for checkerboard method and time killing curve indicated that mefloquine in combination with colistin showed a good antibacterial activity. Furthermore, the combination of these two drugs inhibited biofilm formation and eradicated pre-formed mature biofilms. This synergistic effect was visualized using scanning electron microscopy (SEM), wherein the results showed that the combination of mefloquine and colistin reduced biofilm formation significantly. Further, the application of this combination of drugs to in vivo infection model significantly increased the survival rate of G. mellonella larvae. Altogether, the combination of mefloquine and colistin showed a good synergistic effect in vitro and in vivo, and highlighted its potential to be used as an alternative therapy for the treatment of colistin-resistant P. aeruginosa infection.